Measurement of human tactile sensation capability to discriminate fine surface textures using a variable step-height presentation system - Kawamura, T.; Ohka, M.; Miyaoka, T.; Mitsuya, Y. (1996 IEEE 5th International Workshop on Robot and Human Communication, 1996)
The purpose of this study is to analyze the human sensory information processing of fine-surface textures in three psychophysical experiments. We measured difference thresholds of fine step-height discrimination. These values are important in examining the sensitivity of human mechanoreceptive units. To begin with, we developed a computer-controlled measurement system to present fine step-heights of 0 to 30 /spl mu/m to five human subjects. To obtain the thresholds efficiently, the subjects distinguished between two step-heights presented in a PEST (parameter estimation by sequential testing) trial sequence. In Experiment A, the subjects actively touched the step-heights (active-touch). In Experiment B, they passively touched the step-heights that were driven linearly by an X-table with cyclic movement (passive-touch). In Experiment C they actively touched the step-heights cooled to 15/spl deg/C. The result shows that the thresholds in the active-touch experiment agreed almost with those in the passive-touch experiment. Also, the distinctive sensitivity did not decline even if the step-heights were cooled at 15/spl deg/C.